2022
DOI: 10.3390/ani12121573
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomy of the Palmar Region of the Carpus of the Dog

Abstract: The palmar region of the canine carpus is anatomically complex, and the information found in the literature about its anatomy is inconsistent. The aims of this prospective, descriptive, anatomic study were (1) the clarification and (2) the description of the precise anatomic composition of the palmar region of the canine carpus, with special reference to the canalis carpi. For this study, 92 cadaveric specimens were obtained from 46 dogs that had died for reasons unrelated to this study. Of these, 43 medium-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the veterinary literature the anatomical descriptions regarding its limits and contents vary depending on the consulted source. A recent article suggested that this inconsistency may be related to the non‐differentiation between the two parts of the RF—being the carpal canal limited only by the deep one 12 . Both parts were identified in our study and their ultrasonographic characteristics were documented.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In the veterinary literature the anatomical descriptions regarding its limits and contents vary depending on the consulted source. A recent article suggested that this inconsistency may be related to the non‐differentiation between the two parts of the RF—being the carpal canal limited only by the deep one 12 . Both parts were identified in our study and their ultrasonographic characteristics were documented.…”
Section: Discussionmentioning
confidence: 68%
“…A recent article suggested that this inconsistency may be related to the non-differentiation between the two parts of the RF-being the carpal canal limited only by the deep one. 12 Both parts were identified in our study and their ultrasonographic characteristics were documented. These data have not been previously reported based on our review of the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original publication [ 1 ], there was a mistake in Figure 3. In response to a suggestion from one of the reviewers (point 6 of Reviewer #2), the authors modified some figures to add a schematic drawing.…”
Section: Error In Figurementioning
confidence: 99%